2015
DOI: 10.1210/en.2015-1567
|View full text |Cite
|
Sign up to set email alerts
|

Using a 3D Culture System to Differentiate Visceral Adipocytes In Vitro

Abstract: It has long been recognized that body fat distribution and regional adiposity play a major role in the control of metabolic homeostasis. However, the ability to study and compare the cell autonomous regulation and response of adipocytes from different fat depots has been hampered by the difficulty of inducing preadipocytes isolated from the visceral depot to differentiate into mature adipocytes in culture. Here, we present an easily created 3-dimensional (3D) culture system that can be used to differentiate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 30 publications
5
33
0
Order By: Relevance
“…33,34 As observed in 3T3L1 cells, beclin 1 (4.2-fold, p < 0.0001) and FSP27 (3.9-fold, p < 0.001) were upregulated in differentiated SVF, which was associated with significant lipid accumulation and adiponectin expression (Fig. 5).…”
Section: Fsp27 Was Regulated By the Foxo1-autophagy Axis In Adipocytesmentioning
confidence: 52%
See 1 more Smart Citation
“…33,34 As observed in 3T3L1 cells, beclin 1 (4.2-fold, p < 0.0001) and FSP27 (3.9-fold, p < 0.001) were upregulated in differentiated SVF, which was associated with significant lipid accumulation and adiponectin expression (Fig. 5).…”
Section: Fsp27 Was Regulated By the Foxo1-autophagy Axis In Adipocytesmentioning
confidence: 52%
“…33,34 Briefly, subcutaneous white adipose tissues from C57BL6/J mice (8-12 week old) were dissected, minced, and digested. Cells were suspended in growth media (DMEM/F12 containing 10% FBS and 100 units/ml penicillin and 100 mg/ml streptomycin (1 £ P/S)), filtered through a 100-micron cell strainer, and centrifuged at 500 x g for 5 minutes.…”
Section: Svf Isolation and Culturementioning
confidence: 99%
“…In addition, Yang et al reported that murine adipose derived stromal cells were successfully differentiated into mature adipocytes with BAT pheno-type and function within 3D hydrogels [50]. For WA, 3D culture has been demonstrated to promote adipogenesis and adipokine secretion compared to 2D culture [51,52]. It has also been demonstrated that a porous structure could improve the cell viability in vitro and promote cell ingrowth and integration in vivo [35,53].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to 2D culture systems, 3D hydrogel based culture systems better retain the characteristics of the depot of origin and promote the adipogenic differentiation of adipogenic progenitor and stromal cells [51,60]. Both HA and gelatin have been widely used as adipose tissue engineering biomaterials [24,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…29 Interestingly, VAT stromal cells exhibit additional immunomodulatory properties that may directly or indirectly impact Treg biology, including a heightened secretion of pro-inflammatory cytokines (IL-6 among others) under in vitro conditions, compared with stromal cells isolated from SAT in both humans 69 and mice. 70 Despite recent characterization efforts of VAT and SAT stromal cells at the single-cell level, 27,62,71-73 a more comprehensive analysis using a standardized tissue preparation protocol that yields an accurate representation of all stromal components, as well as consensus markers to render results more comparable, would be very valuable.…”
Section: Depotmentioning
confidence: 99%